Engineering the Stability of Nanozyme-Catalyzed Product for Colorimetric Logic Gate Operations - Lianlian Fu; Deshuai Yu; Dijuan Zou; Hao Qian; Youhui Lin (Molecules, 2021)
Recently, the design and development of nanozyme-based logic gates have received much attention. In this work, by engineering the stability of the nanozyme-catalyzed product, we demonstrated that the chromogenic system of 3, 3′, 5, 5′-tetramethylbenzidine (TMB) can act as a visual output signal for constructing various Boolean logic operations. Specifically, cerium oxide or ferroferric oxide-based nanozymes can catalyze the oxidation of colorless TMB to a blue color product (oxTMB). The blue-colored solution of oxTMB could become colorless by some reductants, including the reduced transition state of glucose oxidase and xanthine oxidase. As a result, by combining biocatalytic reactions, the color change of oxTMB could be controlled logically. In our logic systems, glucose oxidase, β-galactosidase, and xanthine oxidase acted as inputs, and the state of oxTMB solution was used as an output. The logic operation produced a colored solution as the readout signal, which was easily distinguished with the naked eye. More importantly, the study of such a decolorization process allows the transformation of previously designed AND and OR logic gates into NAND and NOR gates. We propose that this work may push forward the design of novel nanozyme-based biological gates and help us further understand complex physiological pathways in living systems.